PENGARUH KELENGKAPAN FASILITAS RECEIVING HOTEL X TERHADAP KINERJA KARYAWAN: Indonesia - Ramadhan, Zahran Ivan; Afriasih, Maria Ulfah Catur; Putri, Liza Amalia (Jurnal Perhotelan dan Pariwisata, 2023)
Receiving is a department that is responsible for the process of receiving goods and equipment for hotel operations. The success of receiving in maintaining the quality of goods when receiving goods is also influenced by the completeness of facilities for receiving goods at receiving.The purpose of this study was to determine the Effect of Hotel X Receiving Facilities on Employee Performance. The population of this study was 33 employees of Hotel X. Data collection techniques used a Google Form questionnaire, conducting observations, documentation, and conducting research on literature studies. This research method is descriptive analysis with a quantitative approach. Data analysis used is a correlation test, determination test, and t test. The results of the study showed that the significance value of 0.844 means there is a significant influence, meaning the level of closeness of the relationship between variables can be said to be strong. So it can be concluded that Ha is accepted, Ho is rejected, then there is an influence between Receiving Facilities on Employee Performance at Hotel X. Hotel X should be able to provide complete and adequate receiving facilities both in terms of facilities and infrastructure, because the availability of complete receiving facilities can support employee work productivity. Keywords: Facilities, Employee Performance